BACTERIAL SYMBIONTS OF REEF’S INVERTEBRATES: A MARINE NATURAL DRUG’S FACTORY - Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Marine invertebrates that are mainly accumulating within coral reef ecosystems such as soft corals, sponges, tunicates, and bryozoans have long been recognized as the prolific sources of structurally unique and diverse natural products since they provide a large proportion of bioactive compounds with different biological activities.Unfortunately, the supply of these bioactive natural products is usually insufficient to meet the ultimate development of most marine natural products. The concentrations of many highly active compounds in reef’s invertebrates are often minute, accounting for less than 10-6% of the wet weight. This problem has been viewed as the most significant threat regarding the development of pharmaceutical from reef’s invertebrates. The secondary metabolites from bacterial symbionts, on the other hand,is a rapidly growing field, due to the suspicion that bioactive metabolites obtained from invertebrates may be produced by their bacterial symbionts. In particular, from sustainability point of view, isolating bioactive-producing bacteria is obviously offers a much better approach than cultivating and harvest invertebrates, which are in most cases extremely difficult.Bacteria isolated from living surfaces, in particular from reef’s invertebrates, are a promising source of natural products. It is expected that still quite a few parts of unexplored culturable bacterial symbionts exists in the reefs. Such information might be desirable, as these bacterial symbionts may serve beneficial purposes as the source of secondary metabolites including novel marine natural products.